2011
DOI: 10.2169/internalmedicine.50.4647
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Myelopathy following Neurogenic Proximal Weakness Associated with Human T-Cell Lymphotropic Virus Type I Infection

Abstract: We report a patient with human T-cell lymphotropic virus type I (HTLV-I) infection, who presented with proximal extremity neurogenic muscular weakness followed by fulminant myelopathy, but with no upper motor symptoms. The symptoms were inconsistent with the World Health Organization or El Escorial criteria for HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP) or amyotrophic lateral sclerosis (ALS). This case indicates that fulminant myelopathy without upper motor neuronal symptoms may occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Atrophy of the thoracic cord in HAM/TSP patients has been reported in many MRI studies, and some patients with HAM/TSP show diffuse T2hyperintensity and swelling of the cervical cord as an inflammatory lesion (Umehara et al, 2007;Yukitake et al, 2008). Although relatively large lesions in the cervical cord by contrast-enhanced MRI are reported (Umehara et al, 2007;Yamashita et al, 2011), multiple spotty lesions as seen in the present patient are rarely reported. When inflammation is strong, it is speculated that multiple spotty lesions join together and show relatively large lesions on MRI.…”
Section: Discussionmentioning
confidence: 46%
“…Atrophy of the thoracic cord in HAM/TSP patients has been reported in many MRI studies, and some patients with HAM/TSP show diffuse T2hyperintensity and swelling of the cervical cord as an inflammatory lesion (Umehara et al, 2007;Yukitake et al, 2008). Although relatively large lesions in the cervical cord by contrast-enhanced MRI are reported (Umehara et al, 2007;Yamashita et al, 2011), multiple spotty lesions as seen in the present patient are rarely reported. When inflammation is strong, it is speculated that multiple spotty lesions join together and show relatively large lesions on MRI.…”
Section: Discussionmentioning
confidence: 46%
“…The rate of progression is variable and seems to be faster in women with premenopausal onset of disease, in subjects with higher proviral loads and in immunosuppressed individuals contracting the infection by transfusion. A rapidly progressive form with acute to subacute onset and complete paraplegia in less than 2 years can also occur (Yamashita, Ueda et al 2011).…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%